Re-identification and Prioritization of Factors Affecting the Reengineering of Sports Businesses with an Emphasis on Customer Relationship Management - Ali Keipour, Naser; Nemati, Nematollah; Abdi, Hassan; Bagherpour, Tahereh (Digital Transformation and Administration Innovation, 2025)
The purpose of this study was to re-identify and prioritize the dimensions and factors influencing the reengineering of sports businesses with an emphasis on customer relationship management. The research method was descriptive–survey, in which quantitative methods, including questionnaire design and the use of statistical techniques, as well as qualitative methods, including interviews with experts and coding, were employed. Initially, the research expert team conducted an in-depth study to examine the theoretical foundations and research background, and to collect and categorize data. Subsequently, through interviews with experts in the field of sports marketing in the country, the factors influencing the reengineering of businesses in sports organizations were re-identified and determined. Experts in this field were consulted to review and validate the extracted factors. In order to prioritize the criteria, the Fuzzy Analytic Hierarchy Process (FAHP) method was used. In total, 12 factors were identified as variables influencing the reengineering of sports businesses, categorized into three dimensions: structural, communicational, and functional. Accordingly, the “structural” dimension, with a weight of 0.52186, ranked highest in importance, followed by the “communicational” dimension, with a weight of 0.52186, and finally, the “functional” dimension, with a weight of 0.39209. Among these, the factor “branding” had the highest weight (0.37122). The next influential factor was “creativity and innovation in the production of goods and the provision of services to users,” with a weight of 0.34289. The least important factor was identified as “designing an attractive and unique environment for the organization,” with a weight of 0.05542. Overall, attention to the three dimensions—structural, communicational, and functional—with an emphasis on their order of priority can help sports marketing managers and planners ensure the effectiveness of their decisions. In this regard, strategic priority lies with branding and creativity and innovation in providing sports goods and services.